MicroRNA-155—at the Critical Interface of Innate and Adaptive Immunity in Arthritis - Alivernini, Stefano; Gremese, Elisa; McSharry, Charles; Tolusso, Barbara; Ferraccioli, Gianfranco; McInnes, Iain B.; Kurowska-Stolarska, Mariola (Frontiers in Immunology, 2018)
MicroRNAs (miRNAs) are small non-coding RNAs that fine-tune the cell response to a changing environment by modulating the cell transcriptome. miR-155 is a multifunctional miRNA enriched in cells of the immune system and is indispensable for the immune response. However, when deregulated, miR-155 contributes to the development of chronic inflammation, autoimmunity, cancer, and fibrosis. Herein, we review the evidence for the pathogenic role of miR-155 in driving aberrant activation of the immune system in rheumatoid arthritis, and its potential as a disease biomarker and therapeutic target.